CYTOIMMUNOGRAM OF THE SKIN: A NEW METHOD FOR OBJECTIVE EVALUATION OF THE SKIN CELL SUBPOPULATION PROFILE - S. V. Goltsov; E. N. Goltsova; Yu. G. Sukhovey; E. G. Kostolomova; V. Yu. Pauls (Медицинская иммунология)
The history of dermatology reminds a lot of attempts to transform the dense human skin samples into a liquid phase. A search for a method aimed to separate cellular substrate of the skin and to obtain a suspension for studying the cell phenotype profile was a basis of our long-term study, which resulted in a proprietary method for digital estimation of distinct subsets composing the skin cell population. The skin cytoimmunogram is the name of the invention, which is recognized as practical and promising for implementation in public healthcare system as recognosed by the decision of the “Xth International Conference of Immunologists of the Urals”, where the report on the “Prospects for application of the skin cytoimmunogram” was presented for the first time. The results of a single case analysis showed the following findings for this skin sample: 1) a subpopulation of keratinocytes is actively represented, most of them activated, which indicates a moderate proliferative activity of the basal layer of the epidermis; 2) there are B-lymphocytes, which normally are residents of the circulating blood and lymph, since they have a positive taxis to the high endothelial venulas located mainly in the lymph nodes. Their presence in the skin indicates the activity of humoral immunity; 3) presence of several T-cell types of (CD+3 lymphocytes) localized predominantly in the three outer layers of the epidermis, and the findings of CD4+ cells predominating over CD8+ cells suggests an increase in adaptive skin immunity; 4) low content of T-cytotoxic cells indicates to absence of an infectious/inflammatory process; 5) the remaining parameters reflect the numbers of specific skin cells, characterized by low activation grade, which, along with absence of specific complaints in this patient, indicates to normal state of his skin; 6) cell viability in the native sample was 99.8%, after cryopreservation – 87.0%. The proposed method allows to obtain information on the quantitative composition and functional activity of skin cells, which distinctly indicates to the present condition of the patient’s local immunity and may become a basis for development of personalized curative and prophylactic programs. The Сytoimmunogram of skin as a way of skin diagnostic evaluation, is easy to implement, and it is available for qualitative and quantitative evaluation of separate cell subpopulations, in order to assess their function and degree of their response to any external or internal environmental impact. Widespread application of the сytoimmunogram perspective will allow to create sex- and age-matched registry for skin parameters in normal and pathological conditions, thus determining the extent of skin response to environmental exposures, to measure activities of cell subsets in native skin under normal and pathological conditions, to justify the criteria of age-related skin changes, to objectively assess clinical course of skin diseases, and to individually select the drug and monitor the effectiveness of external medical drugs applied.